Contract Analysis Reality Judgment T-00117/18 (2021)
This work analytically and structurally frames judgment T-00117/18 within the incidence of the contract for the provision of services as an instrument for linking work in the public sector as the specialized or support human resource for temporary work , the constitutive elements of the labor contract, the reality contract and how jurisprudence determines this category as a flaw in the contractual formality in force within the public sphere and the primacy of the essence over the form in any kind of relationship.